Современная технология проведения акупунктурного термочувствительного диагностического теста Kobei Akabane = Modern technology of acupuncture thermally sensitive diagnostic test Akabane Kobei - I Z Samosiuk; N I Samosyuk; N V Chuhraev; E N Chuhraeva; W A Zukow (Kazimierz Wielki University, 2015)
Samosiuk I Z, Samosyuk N I, Chuhraev N V, Chuhraeva E N, Zukow W A. Современная технология проведения акупунктурного термочувствительного диагностического теста Kobei Akabane = Modern technology of acupuncture thermally sensitive diagnostic test Akabane Kobei. Journal of Education, Health and Sport. 2015;5(2):225-245. ISSN 2391-8306. DOI: 10.5281/zenodo.16094 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A225-245 https://pbn.nauka.gov.pl/works/546171 http://dx.doi.org/10.5281/zenodo.16094 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   Современная технология проведения акупунктурного термочувствительного диагностического теста Kobei Akabane   Modern technology of acupuncture thermally sensitive diagnostic test Akabane Kobei   Самосюк И. З.1, Самосюк Н. И.1, Чухраев Н. В.2, Чухраева Е. Н.1, Жуков В.А.3   Samosiuk I Z1, Samosyuk N I1, Chuhraev N V2, Chuhraeva E N1, Zukow W A3   1Национальная медицинская академия последипломного образования имени П.Л. Шупика 2Научно-методический центр «Медицинские инновационные технологии» 3Uniwersytet Kazimierza Wielkiego w Bydgoszczy   1National Medical Academy of post-graduate education named after P. L. Shupyk 2Scientific-methodical Center "Medical innovation technologies" 3Uniwersytet Kazimierza Wielkiego 3 w Bydgoszczy   Ключевые слова: акупунктурный термочувствительный диагностический тест, Kobei Akabane.   Keywords: acupuncture thermal diagnostic test, Kobei Akabane.   Резюме Использование термочувствительного теста в акупунктурной диагностике существенно облегчает правильный выбор точек воздействия. Высокая информативность теста позволяет рекомендовать его для широкого внедрения в практику акупунктуры.   Abstract Use of a thermal test in acupuncture diagnosis makes the right choice points. High information capacity test allows you to recommend it for wide introduction in the practice of acupuncture.